Inhaled and systemic corticosteroid response in severe asthma assessed by alveolar nitric oxide: a randomized crossover pilot study of add‐on therapy. (14th December 2012) - Williamson, Peter A.; Short, Philip M.; Vaidyanathan, Sriram; Lipworth, Brian J.
<x xml:space="preserve">Abstract</x> WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT Extra fine inhaled corticosteroid formulations such as HFA beclomethasone may be used to target the small airways in asthma. However, it is unclear which outcome measures may detect such small airways effects in patients with severe asthma. WHAT THIS STUDY ADDS The alveolar fraction of exhaled nitric oxide is not a sensitive outcome measure for following effects of extra fine particle inhaled beclomethasone in severe asthma. However there were significant effects on nitric oxide fractions measured at 50 ml s−1 and bronchial flux with the extra fine formulation, which did not produce significant cortisol suppression. AIMS Alveolar nitric oxide (CANO) is a potential biomarker of small airway inflammation. We investigated effects on CANO of the addition of coarse and fine particle inhaled corticosteroids to standard therapy in severe asthma. METHODS Severe asthmatics taking ≥1600 µg day−1 budesonide or equivalent performed a randomized open‐label crossover study. Subjects with FEV1 < 80%, gas trapping and CANO≥2 ppb entered a 6 week dose‐ramp run‐in of fluticasone/salmeterol(FPSM) 250/50 µg twice daily for 3 weeks, then 500/50 µg twice daily for 3 weeks. Patients then received additional HFA‐beclomethasone diproprionate (BDP) 200 µg twice daily or FP 250 µg twice daily for 3 weeks in a crossover. Participants then received prednisolone(PRED) 25 mg day−1 for 1 week. Nitric oxide, lung function, mannitol challenge, systemic inflammatory markers and urinary cortisol were measured. RESULTS Fifteen completed per protocol: mean (SD) age 51 (12) years, FEV1 58 (13)% predicted, residual volume 193 (100)% predicted and mannitolPD10 177 (2.8) µg. There was no significant difference between FPSM and add‐on therapy for CANO. FPSM/BDP and FPSM/PRED suppressed broncial flux (JawNO) and FENO compared with FPSM alone, but there was no significant difference between FPSM/BDP and FPSM/FP. ECP, e‐selectin and ICAM‐1 were suppressed by FPSM/PRED compared with FPSM and FPSM/FP but not FPSM/BDP. Plasma cortisol was significantly suppressed by FPSM/PRED. CONCLUSION In severe asthma, CANO is insensitive to changes in dose and delivery of inhaled corticosteroids and is not suppressed by systemic corticosteroids. Additional inhaled HFA‐BDP reduced FENO and JawNO without adrenal suppression. There was a trend to reduction in FENO and JawNO with additional FP but this did not reach statistical significance. PRED reduced FENO and JawNO with suppression of systemic inflammatory markers and urinary cortisol.